(untitled) (Asian Journal of Agriculture, 2022)
Abstract. Eagleton GE. 2022. A daylength-neutral winged bean (Psophocarpus tetragonolobus) for Southern Australian latitudes. Asian J Agric 6: 68-78. In the summer of 2019, on the central coast of NSW, Australia (at Latitude 34°S), an early-maturing genotype of the tropical legume crop, winged bean (Psophocarpus tetragonolobus (L.) DC.), was detected among a range of late-maturing accessions. The performance of this accession, MY0-01 from Bago in Myanmar, was evaluated in staked plots alongside one other accession from Myanmar and two from the island of New Guinea planted on three successive occasions between October and late November 2020 in a split-plot experiment. Across the three planting dates, the mean number of days from planting to the first open flower for MYO-01 ranged from 68 to 82 + s.e. 3.2 compared with a range of 119 to 167 for the other three accessions. The mean accumulated seed yield of MYO-01 obtained from the October planting equated to 3.1 t ha-1, but by the third planting in late November, the yield was only half as much. Among the four accessions, MYO-01 was second in the amount of lower stem branching and tuber yield, with the smallest pods and hardest seeds. Hard seededness creates difficulties for germination and plant establishment and is a limitation in MYO-01, as are its small pods, which lowers its potential for vegetable production. Investigating genetic control of photoperiod insensitivity in MYO-01 and combining the ability for pod and seed characteristics is relevant to sub-tropical latitudes and for developing stable early maturity cultivars for the tropics.